Novel paradigms to measure variability of behavior in early childhood: posture, gaze, and pupil dilation - Hepach, Robert; Vaish, Amrisha; Tomasello, Michael (Frontiers in Psychology, 2015)
A central challenge of investigating the underlying mechanisms of and the individual differences in young children’s behavior is the measurement of the internal physiological mechanism and the involved expressive emotions. Here, we illustrate two paradigms that assess concurrent indicators of both children’s social perception as well as their emotional expression. In one set of studies, children view situations while their eye movements are mapped onto a live scene. In these studies, children’s internal arousal is measured via changes in their pupil dilation by using eye-tracking technology. In another set of studies, we measured children's emotional expression via changes in their upper-body posture by using depth sensor imaging technology. Together, these paradigms can provide new insights into the internal mechanism and outward emotional expression involved in young children’s behavior.